Analisis Program Adiwiyata Dalam Menanamkan Sikap Peduli Lingkungan di Sekolah Dasar - Nisa, Annisa Qomariah; Handayani, Eka Selvi; Elisthina, Elisthina (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research is a descriptive research method with the aim of describing the analysis of the Adiwiyata program to instill an attitude of caring for the environment in elementary schools. Data collection techniques were carried out using interviews and documentation. The instruments used in this research were an interview guideline, an interview guide for school principals, teachers and students. In testing the validity of the data, researchers used source triangulation. The subjects in this research were school principals, students and teachers. From the data obtained by researchers, the Adiwiyata program to instill an attitude of caring for the environment in elementary schools is considered good. Judging from the lack of waste, tree planting, air and electricity use. And the disadvantages are the lack of parking space, the narrow school environment. It needs to be removed from environmental concerns, a challenge that must be faced as a responsibility of the school community. Teachers must be able to provide students with an understanding of caring about the school environment and at home so that students can get used to good habits. Keywords: Adiwiyata Program, Attitude, Environmental Care